2000
DOI: 10.1054/bjoc.2000.1379
|View full text |Cite
|
Sign up to set email alerts
|

Major hepatic resection may suppress the growth of tumours remaining in the residual liver

Abstract: Little is known as to how hepatectomy is associated with the growth of hepatic tumours, which may reside in the remaining liver after curative resection for hepatocellular carcinoma. Using an intra-hepatic tumour implantation model in rats, the effects of hepatectomy on tumour growth in the remaining liver were investigated. On post-operative day 7, the tumour weight in the remaining liver following 30% hepatectomy was 0.321 ± 0.058 g (mean ± SD) which was significantly greater than that (0.245 ± 0.040 g) in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
(29 reference statements)
2
15
1
Order By: Relevance
“…It was also not clarified whether systemic application of DPO may exert growth stimulation on tumor cells at extrahepatic sites. This, however, is of particular interest, because previous studies have shown that extra- and intrahepatic tumor growth may be differentially influenced by liver regeneration after hepatectomy [28,29]. We herein demonstrate now for the first time that systemic application of DPO also promotes colorectal tumor cell engraftment and growth at extrahepatic sites.…”
Section: Discussionsupporting
confidence: 50%
“…It was also not clarified whether systemic application of DPO may exert growth stimulation on tumor cells at extrahepatic sites. This, however, is of particular interest, because previous studies have shown that extra- and intrahepatic tumor growth may be differentially influenced by liver regeneration after hepatectomy [28,29]. We herein demonstrate now for the first time that systemic application of DPO also promotes colorectal tumor cell engraftment and growth at extrahepatic sites.…”
Section: Discussionsupporting
confidence: 50%
“…The restoration of the hepatic volume occurs within 1 week, independent of the hepatic removal volume [27] . Based on this information, we measured the pre-and postoperative serum levels of HGF, EGF, VEGF and TGF-· during 5 days after liver resection.…”
Section: Discussionmentioning
confidence: 97%
“…This might be explained by the presence of human inhibitory (anti-HGF) factors in the patients' serum. In this context, Yokoyama et al [27] showed that major hepatic resection suppressed the growth of the tumor in the remnant liver. Moreover, major resection caused the expression of apoptosis-related genes and secretion of inhibitory growth factor, such as TGF-ß [27] .…”
Section: Discussionmentioning
confidence: 99%
“…23 Briefly, AH-130 cells were maintained by intraperitoneal passage in male Donryu rats every 7-8 days. A suspension of AH-130 tumor cells was prepared in Hanks' balanced salt solution (HBSS), at a concentration of 5 ϫ 10 6 cells/ml, and 1 ml was injected into the flank of Donryu rats.…”
Section: Methodsmentioning
confidence: 99%